EXPLORING STUDENTS' DIFFICULTIES AND STRATEGIES IN LEARNING ENGLISH GRAMMAR AT ENGLISH EDUCATION STUDY PROGRAM - Kesaulya, Gabriella; Lekawael, Rosina; Rijoly, Helena (Pattimura University, 2024)
This study aimed to identify the difficulties in learning English Grammar and their strategies to overcome it. The researcher used mixed method with the explanatory sequential mixed methods design. This method involved a two-part project in which the researcher collects quantitative data in the first phase, analyzes the results, and then used the results to develop the qualitative part in the second phase. This research took in English education study program, Pattimura University during this year. Batch 2022 was the subject and 99 students were the population. For the sample, Class A which had 32 students and 6 students were selected as the interview participants. The result showed that material and structural difficulties, as well as psychological difficulties, contributed significantly to the overall difficulties experienced by the participants. Furthermore, students learning strategies to overcome their difficulties in learning English, the data suggests that participants in this study employ a diverse range of strategies to support their learning. While all strategies are utilized, metacognitive strategies and affective strategies seem to be particular prominent. Students also agree that psychological difficulties affect students' ability to learn grammar, particularly fear of mistakes and confidence issues. The last that each student has different learning strategies in overcoming the difficulties that exist. All six students have explained how they overcome their difficulties in learning grammar as well as the psychological difficulties that have affected their ability to learn English grammar. The investigation emphasizes the importance of metacognitive and affective strategies in overcoming psychological difficulties to learning grammar.